Muscular Christian Themes in Contemporary American Sport: A Case Study - Andrew R. Meyer (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2012)
Muscular Christianity is often credited as being influential in Western sport ideology but is rarely mentioned in contemporary analysis. This paper identifies instances of muscular Christian ideals, as defined by Thomas Hughes, observable in the contemporary American sport context, addressing the continued religious impact of sport. Muscular Christian themes were identified in various media, including, online videos, magazines, books, and commercials involving American cyclist Lance Armstrong. Two of Hughes’ themes were observable in the media portrayal of Armstrong: a body used for the protection of the weak and a body used for the advancement of all righteous causes. These findings suggest that themes Hughes identified as muscular Christian continue to operate in the contemporary American sport context, observable through media portrayals of athletes.
Keywords: Sport; faith-based; leisure; spirituality; muscular Christianity